Corneal Topographic and Aberrometric Measurements Obtained with a Multidiagnostic Device in Healthy Eyes: Intrasession Repeatability - David P. Piñero; Alberto López-Navarro; Inmaculada Cabezos; Dolores de Fez; María T. Caballero; Vicent J. Camps (Journal of Ophthalmology)
Purpose. To evaluate the intrasession repeatability of corneal curvature, eccentricity, and aberrometric measurements obtained with a multidiagnostic device in healthy eyes. Methods. This study enrolled 107 eyes of 107 patients ranging in age from 23 to 65 years. All of them underwent a complete anterior segment examination with the VX120 system (Visionix-Luneau Technologies, Chartres, France). Three consecutive measurements were obtained. The within-subject standard deviation (Sw), intrasubject precision (1.96×Sw), and intraclass correlation coefficient (ICC) were calculated. Results. All Sw for corneal power measurements were below 0.26 D, with ICC above 0.982. The Sw for corneal astigmatism at different areas (3, 5, and 7 mm) was below 0.21 D, with ICC above 0.913. Concerning the axis of astigmatism, its Sw was below 11.27°, with ICC above 0.975. The Sw and ICC for corneal eccentricity were 0.067 and 0.957, respectively. The Sw and ICC for high-order aberration root mean square (RMS) were 0.048 µm and 0.901, respectively. For 3rd- and 4th-order aberrometric parameters, all Sw were below 0.037 µm and all ICC were higher than 0.84, except for quadrafoil RMS (ICC: 0.689). Conclusions. The multidiagnostic device evaluated is able to provide consistent measurements of corneal power, eccentricity, and third- and fourth-order aberrations in healthy eyes.